2002
DOI: 10.1001/archotol.128.8.928
|View full text |Cite
|
Sign up to set email alerts
|

Exclusively Endoscopic Removal of Juvenile Nasopharyngeal Angiofibroma

Abstract: An exclusively endoscopic management of juvenile nasopharyngeal angiofibroma appears to be effective for small to medium tumors. It should be considered as a first-choice option for these cases (in view of the minimal bleeding, shorter duration, and efficacy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 34 publications
5
111
0
4
Order By: Relevance
“…Since this is a nasal approach, endoscopy brought about not only less invasion, but also better cosmetic results and less surgery time. This was seen in the present study, in which average surgical time was of 102 minutes, matching reports considered satisfactory in the literature 7 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Since this is a nasal approach, endoscopy brought about not only less invasion, but also better cosmetic results and less surgery time. This was seen in the present study, in which average surgical time was of 102 minutes, matching reports considered satisfactory in the literature 7 .…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that the endoscopic procedure is effective only for the total removal of small and intermediary size tumors [5][6][7][8] ; notwithstanding, there are studies that favor even the removal of tumors that extend to the pterigoid fossa and limited to the cranial fossa 9 . However, the debate remains, because studies have shown recur- (from 2 to 7 days) (Figures 1 and 2).…”
Section: Fisch or Chandlermentioning
confidence: 99%
See 1 more Smart Citation
“…4 -24 The largest series was a retrospective study of 20 cases from six academic referral hospitals; the authors found the endoscopic approach to be the first choice for small to mediumsized angiofibromas. 14 In their experience of 15 cases, Nicolai et al found the endoscopic approach to be safe and effective. 20 Endoscopic exposure and excision is considered to be the first choice of surgical approach in cases of limited angiofibroma involving the posterior part of the nasal cavity, nasopharynx, sphenoid sinus and pterygopalatine fossa.…”
Section: Discussionmentioning
confidence: 99%
“…The internal maxillary artery can be either clipped 20 or diathermised. 14 Endoscopic tumour removal in the infratemporal, parapharyngeal and pterygomaxillary regions can be supplemented with sublabial and buccolabial incisions. 19 The tumour should be excised in the submucosal and subperiosteal planes, displaced and then finally delivered either transnasally or transorally.…”
Section: Discussionmentioning
confidence: 99%